Attachment Patterns in Subjects Diagnosed With a Substance Use Disorder: A Comparison of Patients in Outpatient Treatment and Patients in Therapeutic Communities - Vismara, Laura; Presaghi, Fabio; Bocchia, Maria; Ricci, Rosolino Vico; Ammaniti, Massimo (Frontiers in Psychiatry, 2019)
The purpose of the present study is to analyze the quality of attachment in substance abuse patients in outpatient treatment vs. patients in therapeutic communities in order to identify the role of attachment insecurity in choosing a care system. The sample consisted of 127 subjects (107 males and 20 females); 97 were outpatients (83 males) and 30 therapeutic community patients (24 males). Attachment with respect to current, significant relationships as assessed using the Relationship Questionnaire. In the outpatient subgroup, the prevailing attachment style was preoccupied; for the therapeutic community patients, the prevailing attachment style was dismissive. Care, that is how the subject experienced as a child her caregiver as loving and caring or cold and withdrawn, and overprotection, that is how the parent was experienced as intrusive and infantilizing or supportive of autonomy (evaluated using the Parent Bonding Instrument ), were higher for outpatients, and scores were higher with respect to maternal sub-scales regardless of treatment modality. No differences emerged with respect to self-perceived symptoms (SCL-90-R) between the subgroups; however, fearful-avoidant and dismissive-avoidant individuals reported higher self-perceived symptom regardless of treatment modality. Understanding the distribution of different attachment patterns with respect to the treatment modality may improve efficacious interventions, attuning them to the individual and his or her developmental environment.